The Screening Test for Emotional Problems – Teacher-Report Version (STEP-T): Studies of Reliability and Validity. (April 2015) - Erford, Bradley T.; Butler, Caitlin; Peacock, Elizabeth
The Screening Test for Emotional Problems – Teacher Version (STEP-T) was designed to identify students aged 7–17 years with wide-ranging emotional disturbances. Coefficients alpha and test-retest reliability were adequate for all subscales except Anxiety. The hypothesized five-factor model fit the data very well and external aspects of validity were excellent.